2021
DOI: 10.1002/ece3.7275
|View full text |Cite
|
Sign up to set email alerts
|

“Micropersonality” traits and their implications for behavioral and movement ecology research

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…The lack of a link between motion in the start box and leadership could indicate that motion captured prior to free-swimming does not reflect "activity" as measured in other behavioral studies (Carter et al 2013). However, this finding is similar to other work with stickleback fish shoals (of the same shoal size) that did not find links between exploratory tendency and leadership (Jolles et al 2017), and a recent study of our fish population has found finescale motion and broad-scale behavioral parameters are broadly equivalent, suggesting value in this approach (Bailey et al 2021). Future work should now focus on between-individual variation in how fish balance goal-oriented movement and socially oriented behaviors (Conradt et al 2009) and attempt to measure this trade-off (sticking with others versus moving away from them) in-situ during controlled experiments, and in different contexts (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of a link between motion in the start box and leadership could indicate that motion captured prior to free-swimming does not reflect "activity" as measured in other behavioral studies (Carter et al 2013). However, this finding is similar to other work with stickleback fish shoals (of the same shoal size) that did not find links between exploratory tendency and leadership (Jolles et al 2017), and a recent study of our fish population has found finescale motion and broad-scale behavioral parameters are broadly equivalent, suggesting value in this approach (Bailey et al 2021). Future work should now focus on between-individual variation in how fish balance goal-oriented movement and socially oriented behaviors (Conradt et al 2009) and attempt to measure this trade-off (sticking with others versus moving away from them) in-situ during controlled experiments, and in different contexts (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Recent work with our study population of stickleback fish has shown that fine-scale measures of fish motion and broad-scale behavioral parameters that are commonly used in animal personality research are broadly equivalent ( Bailey et al 2021 ). We, therefore, measured fish motion in their start boxes ( Figure 1c ) using a custom-made routine (implemented in C++ using OPENCV library, Bradski 2000 ) and expected this to represent a measure of fish “activity”.…”
Section: Methodsmentioning
confidence: 99%
“…Because the location was collected at a 1 Hz frequency the number of points is equal to the number of seconds spent in the area. These five behaviours were selected because they are the most commonly studied movement behaviours in animal personality studies [ 31 , 32 , 39 , 40 ], and because in our view they each capture a different and interesting behavioural aspect of individuals' movement and space use. The length of the time units was chosen to have sufficient temporal resolution while also reducing autocorrelation [ 41 ] and enabling the computation of site fidelity by comparing multiple data points over a time period.…”
Section: Methodsmentioning
confidence: 99%
“…This type of data provides the granularity required for the analysis of inter- and intra-individual variability in behaviour and provides the opportunity to achieve a reliable and objective measures of animal personality and predictability [ 19 , 29 ]. For example, measures of movement and space use show inter- and intra-individual variation in both wild and captive animals [ 30 32 ], and such data can easily be collected by modern sensor technologies in farms. Movement behaviours are intrinsically linked with many classically defined personality traits such as ‘exploration’, which is defined by the reaction of an individual towards new environments or objects [ 14 , 31 , 33 ], and ‘activity’, which corresponds to a measure of the amount of movement performed by an individual [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We checked the model and estimation of repeatability of each calling behaviour and call parameters for outliers, heterogeneity of residuals, and variable collinearity to ensure model assumptions were not violated (Zuur et al 2010 ; Zuur & Ieno 2016 ). Although the number of male individuals tested in this study was limited, the models were not overfitted, and the estimation of repeatability was considered reasonable (Bailey et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%